Dīwān Ruʾba Ibn-al-ʿAǧǧāǧ bi-šarḥ Muḥammad Ibn-Ḥabīb - Ruʾba Ibn-al-ʿAǧǧāǧ 690-762; Ibn-Ḥabīb, Muḥammad -860 (Dār ar-Rayāḥīn)
Arabic poetry, 750-1258; history and criticism
Keywords: Ruʼbah ibn al-ʻAjjāj / -762? / Criticism and interpretation; Ruʼbah ibn al-ʻAjjāj / -762?; Arabisch; Lyrik; Anthologie